Small-sided soccer games on sand are more physically demanding but less technically specific compared to games on artificial turf - Rago, V.; Rebelo, A. N.; Pizzuto, F.; Barreira D. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The use of sand has been suggested as fitness-enhancing surface in field-based team sports. However, concerns have arisen in regard whether physical responses associated to sand training are sport-specific. We compared physical and technical demands during small-sided soccer games (4 vs. 4 + goalkeeper; SSGs) played on artificial turf and on sand.